In vitro study of the biocompatibility of materials processed by Additive Manufacturing - Silva, Pedro Miguel Moutinho da (2022)
Trabalho de Projeto do Mestrado Integrado em Engenharia Biomédica apresentado à Faculdade de Ciências e Tecnologia